Cardioversion of suspected vagally mediated atrial flutter using lidocaine in an anaesthetised dog. Issue 2 (7th May 2018) - Cornacchini, Gianmarco; Pedro, Brigite; Martin, Mike; Mair, Alastair
Abstract : A 10‐year‐old male neutered English bull terrier was referred for investigation of sneezing and stertorous breathing. Upper airway assessment under general anaesthesia was scheduled, along with a CT scan, bronchoscopy and bronchoalveolar lavage. The anaesthetic protocol consisted of acepromazine and butorphanol for premedication, propofol for induction, and isoflurane for maintenance of anaesthesia. Laryngoscopy during induction of anaesthesia revealed paradoxical collapse of both arytenoid cartilages with complete closure of the rima glottidis during inspiration. During bronchoscopy an electrocardiogram was attached which revealed atrial flutter. Atrial flutter was converted using lidocaine into a marked respiratory sinus arrhythmia. Six days later the dog was readmitted for unilateral cricoarytenoid lateralisation. No intraoperative or postoperative complications were encountered. It was speculated that atrial flutter was vagally mediated and occurred acutely during laryngoscopy. If atrial flutter is considered to be vagally mediated, lidocaine may serve as a useful treatment.